Body size and its effects on productive efficiency of cows with predominant Nellore genetic composition (Acta Scientiarum. Animal Sciences, 2018)
This study was developed to evaluate productive efficiency during the lactation period of cows with predominant Nellore genetic composition based on their body size. Cows were divided into the following categories: light (â‰¤ 316 kg), moderate (â‰¥ 317 and â‰¤ 400 kg), or heavy (â‰¥ 401 kg). Body weight change and total gain from birth to 210 days of age of calves born from heavy cows (0.155±0.03 and 111.6±5.1 kg) were higher than those of calves born from light (0.064±0.03 and 91.0±4.3 kg) and moderate (0.144±0.03 and 97.7±4.0 kg) cows. Calf production index differed (p < 0.05) with the herd of heavy cows (93.5±3.2 kg), producing 57.4 and 19.7% more kilograms of calf than light (59.4±2.7 kg) and moderate (78.1±2.4 kg) cows, respectively. Heavy Nellore cows produce heavier calves and have a better reproductive performance, which lead to a better calf production index. However, they require a larger area for the same herbage allowance. Calves born from heavier Nellore cows gain more weight from birth to 210 days of age and are heavier from 210 to 270 days of age.